Strategi Pemasaran Bisnis Internasional Pada UMKM Pasar Petisah Di Masa COVID 19 - Bunga Mawar; Nuri Aslami (LPPM Universitas Labuhanbatu, 2021)
This study aims to determine the Marketing Strategy for the Sale of UMKM In Petisah Market In The Covid 19. The research methodology used is qualitative approach qualitative research is research that serves as the data based on the results of the documentation which can give you a clear picture of the object under study, and then in the process and in the analysis to then draw conclusions. Methods of data analysis used is qualitative data that is used in research to explain an object or phenomenon based on the things that generally can not be calculated using the data documentation, literature studies, and secondary data.As the development of the business world, UMKM need to pay more attention to the competition in the business world, both in domestic and abroad. If UMKM want to remain competitive with other companies, UMKM need to pay attention to the main problems, namely marketing. Strategy pemasaranproduk when The Pandemic Covid-19 Effective that :offers a service or product to customers who need help, use the right tools, maximized can be either old features or new features that suit the needs of the community or customers, avoid all the negative impressions that can damage the business.